Factors Affecting The Achievement Of The Student's Learning Outcomes Faculty Of Public Health During Online Learning During The Covid-19 Pandemic - Zamila, Zakya; Hinga, Indiati A. Tedju; Riwu, Yuliana Radja (Faculty of Public Health, Nusa Cendana University, 2020)
The COVID-19 pandemic is a global health threat with the highest number of deaths. Government efforts to disrupt the chain of transmission of Covid-19 by implementing online learning. The shift in teaching methods from face-to-face to online lectures has an impact on student performance. The aim of this study is to describe the factors related to student performance at the Faculty of Public Health during the online lecture during the COVID-19 pandemic. This type of research is descriptive. The population in this study were students from the Faculty of Public Health in semester IV and VI who had given face-to-face lectures as well as online lectures with a total sample of 85 people in a stratified random sample. the result showed that the lerning performance of the student of faculty of public health in online lectures increased with the learning motivation of the students in the middle category namely 81 people (95.2%). The family factor for online lectures was in the middle range, namely 51 people (65%). The students learning facilities are in the high category, namely 74 people (87%), while the students with facilities in the lower category are 5 people (5.88%). Instructor suggestion can improve service quality during online lectures to improve student performance.